DEKADENSI MORAL PADA SPIRITUALITAS ANAK REMAJA KRISTEN DI ERA DIGITAL - Lydia Weniati Augustiana; Ida Lestari (Universitas Kristen Immanuel, 2024)
This descriptive research aims: First, to explain the important points related to the factors that influence the moral and spiritual decadence of Christian teenagers. Second, to explain the Bible's record of the spiritual moral decadence of mankind. The type and method used is qualitative research with descriptive methods with library data sources. The results of this research are: First, the factors that influence the moral and spiritual decadence of Christian teenagers, namely: Changes in the political field, population explosion and urbanization, the rise of world religions. Both moral decadences are found in the Biblical record (Gen. 19-Sodom and Gomorrah; Gen. 6-8 in the time of Noah). Third, efforts to deal with the moral decadence of Christian teenagers are a new birth through the work of Jesus, emphasizing spiritual values and life, responding wisely to the era of digitalization.